Scope of Improvement in the Functioning of National Regulatory Authority—A Step Toward International Accreditation: A Qualitative Study From Pakistan. (November 2019) - Ikram, Raazeyah; Saqib, Anum; Mushtaq, Irem; Atif, Muhammad
Background: International accreditations of drug regulatory authorities not only lead to improvement in their functioning but pharmaceutical firms are also benefited. The aim of this study is to identify aspects that should be improved for the purpose of international accreditation and recognition of Drug Regulatory Authority of Pakistan (DRAP). Methods: A qualitative study was conducted from May 1, 2017, to July 31, 2017. The data were collected from officials working in DRAP through in-depth semistructured interviews. The respondents were recruited through a convenience sampling strategy. The sample size was determined by using the saturation point criterion. Data were analyzed to draw conclusions using inductive thematic analysis. Results: A total of 12 officials working in DRAP were interviewed. Analysis of the data yielded 25 categories, 10 subthemes, and 3 themes. The themes were administrative barriers, operational barriers, and future aspects of international accreditation. The subthemes related to administrative barriers included human resource, lack of harmonization and coordination, transparency and accountability, and improper resource allocation. The subthemes related to operational barriers included procedures and policies, deficit of testing laboratories and equipment, reporting system for adverse drug reactions, and external factors influencing the functioning of DRAP. The subthemes related to future aspects of international accreditation included advantages associated with international accreditation and time required to achieve this goal. Conclusions: There is a huge scope of improvement in the functioning of DRAP and the identified barriers must be dealt with timely to make it happen.